Determinación de zearalenona por cromatografía líquida de alta resolución : normalización de un nuevo método para raciones especiales para cerdos - Cover, Janaína Susan (2013)
The aim of this work was to offer a new method of high performance liquid chromatography (HPLC) to evaluate commercial swine rations (CSR) contaminated by zearalenone (ZEA). After ZEA extraction and purification from CSR, the samples were eluted with acetonitrile, methanol and water solvent system. The results indicated that the proposed method showed to be rapid and efficient for the detection and quantification of ZEA in CSR, since its recovery was 102.62%, it offered excellent precision with a coefficient of variation of 0.9992. Furthermore, it is also proposed a as a biocontrol assay for micotoxigenic fungi isolated and maintained in the laboratory. The test was performed with the killer yeast Trichosporum insectorum CBS 10422 against Fusarium sp and Aspergillus flavus, which demonstrated to be effective against the latter.